Personality, Social Support, and Quality of Life as Determinants of Coping Behavior among Visually Impaired Individuals - Henry O. Imhonde; Olubuogu A. U.; Lina Handayani (Journal of Education and Learning (EduLearn), 2017)
This study examined personality, social support, and quality of life as determinant of coping behaviour among the visually impaired individuals. Fifty (50) visually impaired individuals drawn from Benin City participated in the study. Four hypotheses were stated and tested using independent t. test and regression analysis. The results confirmed three out of the four hypotheses stated.  High social support was found to significantly determine high coping behaviour (t = 3.261, df 48, P less than 0.05), high quality of life significantly determine high coping behaviour (t = 5.136, df 48, P less than 0.05), and that personality, social support, and quality of life jointly predict coping behaviour among visually impaired individuals (R =0.647, R2 = 42%, F(34.626) =; P less than 0.001). Based on the findings of this study, it is recommended that parents/guardians, teachers/counselors of visually impaired individuals should not relent in supporting them. Also relevant authorities should facilitate programmes that will enhance quality of life of individuals with visual impairment to enable them cope better.